Perancangan Sistem E-Voting Mahasiswa Berbasis Web Menggunakan RUP untuk Efisiensi Pemilihan Ketua Organisasi Kampus - Rahayu, Raden Erwin Gunadhi; Kurniadi, Dede; Pratama, Reifalga Gais (Jurnal Algoritma, 2025)
The Student Executive Board (BEM) is an intra-campus student organization that serves as the executive body at the university level, led by a BEM president. Currently, the BEM election is conducted conventionally, resulting in a decline in voter participation due to factors such as students being on vacation, having class schedules, or lacking interest in organizational activities. Therefore, a more effective election process is needed—one solution being the implementation of E-Voting, which allows all students to participate digitally. The objective of this study is to develop an e-voting system that facilitates students in electing the BEM president of the Institut Teknologi Garut, making it easier for them to exercise their voting rights. The method used is the Rational Unified Process (RUP), which consists of four main phases: Inception, Elaboration, Construction, and Transition. The black box testing results indicate that all system functions operate according to the defined scenarios. Meanwhile, beta testing involving 33 respondents achieved a satisfaction rate of 88.48%, categorized as strongly agree. These results demonstrate that the developed e-voting system meets users’ functional requirements, simplifies the committee’s work in managing the election process, and provides students with convenient access to candidate information, vision and mission statements, as well as real-time election results. The contribution of this research lies in presenting an e-voting system that is not only efficient, dynamic, and flexible but also developed using the iterative RUP methodology, ensuring software quality and alignment with student organizational needs. Moreover, it serves as a reference for implementing digital voting technology within academic environments.